2017
DOI: 10.1089/cbr.2016.2141
|View full text |Cite
|
Sign up to set email alerts
|

A Radiolabeled Fully Human Antibody to Human Aspartyl (Asparaginyl)β-Hydroxylase Is a Promising Agent for Imaging and Therapy of Metastatic Breast Cancer

Abstract: There is a need for novel effective and safe therapies for metastatic breast cancer based on targeting tumor-specific molecular markers of cancer. Human aspartyl (asparaginyl) b-hydroxylase (HAAH) is a highly conserved enzyme that hydroxylates epidermal growth factor-like domains in transformation-associated proteins and is overexpressed in a variety of cancers, including breast cancer. A fully human monoclonal antibody (mAb) PAN-622 has been developed to HAAH. In this study, they describe the development of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Sturla et al [63] showed that SMI MO-I-1100 and MO-I-1151 significantly reduced viability and directional motility of glioblastoma multiforme (GBM) cells, and similar effects were observed in GBM cells using lentivirus-sh-ASPH construct, confirming the role of ASPH in these processes [63]. Revskaya et al indicated that radiolabeled human monoclonal antibody (mAb) PAN-622 targeting ASPH on the surface of cancer cells is a promising approach in imaging and, possibly, treatment of metastatic breast cancer [64]. In addition, antisense oligodeoxynucleotide inhibition of ASPH expression significantly reduced the motility of cholangiocarcinoma cells [65] and small interfering RNAs (siRNAs) targeting the exon 2 of ASPH gene inhibited the expression of ASPH and reduced directional motility in HCC cells [22].…”
Section: Therapeutic Approaches Targeting Asphmentioning
confidence: 69%
“…Sturla et al [63] showed that SMI MO-I-1100 and MO-I-1151 significantly reduced viability and directional motility of glioblastoma multiforme (GBM) cells, and similar effects were observed in GBM cells using lentivirus-sh-ASPH construct, confirming the role of ASPH in these processes [63]. Revskaya et al indicated that radiolabeled human monoclonal antibody (mAb) PAN-622 targeting ASPH on the surface of cancer cells is a promising approach in imaging and, possibly, treatment of metastatic breast cancer [64]. In addition, antisense oligodeoxynucleotide inhibition of ASPH expression significantly reduced the motility of cholangiocarcinoma cells [65] and small interfering RNAs (siRNAs) targeting the exon 2 of ASPH gene inhibited the expression of ASPH and reduced directional motility in HCC cells [22].…”
Section: Therapeutic Approaches Targeting Asphmentioning
confidence: 69%
“…Breast cancer [102] Bi-Anti-hCD138 Antibody TAT of 7.4 MBq and 11.1 MBq significantly improved survival (p = 0.0303 and p = 0.0070, respectively), whereas HIPEC and HIPEC + TAT treatments did not significantly ameliorate survival as compared to the control group.…”
Section: Bi-mx35-mabmentioning
confidence: 89%
“…As ASPH is a type II transmembrane protein, its Cterminus carrying the enzymatic domain is exposed outside cells and can be bound by antibodies that can be used for diagnostic and therapeutic purposes. Development of ASPH-specific antibodies has been described in several articles [101][102][103][104][105]. The human IgG1 PAN-622 recognizes the catalytic domain of ASPH.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…This antibody is not directly cytotoxic for tumor cells but is internalized and can deliver cytotoxic moieties into cells [84]. In the subsequent study with a mouse model of metastatic breast cancer, PAN-622 was used for bioimaging and radioimmunotherapy with promising results [104]. Mouse IgG1 monoclonal antibody binding to the C-terminal ASPH domain mediated ADCC by human NK cells [103].…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%